Psychosocial Factors and Adjustment to Pain in Individuals with Postpolio Syndrome - Hirsh, Adam T. (2010)
OBJECTIVE: The purpose of the current study was to examine the associations among measures of psychosocial factors, pain, and adjustment in persons with postpoliomyelitis syndrome. DESIGN: A cross-sectional survey design was used. Sixty-three community-dwelling individuals with postpoliomyelitis syndrome returned completed questionnaires (71% response rate) that included measures of pain intensity and interference, psychological functioning, pain catastrophizing, social support, and pain-related beliefs and coping. RESULTS: After controlling for demographic variables, the group of psychosocial variables accounted for an additional 23% of the variance in pain intensity. These variables explained an additional 35% and 50% of the variance in pain interference and psychological functioning, respectively, after accounting for demographic variables and pain intensity. Social support was associated with both psychological functioning and pain interference, whereas catastrophizing was most closely related to psychological functioning. Individual pain beliefs and coping strategies were variably related to the three criterion measures. CONCLUSIONS: The overall results of the current study are consistent with a biopsychosocial framework for understanding pain and functioning in individuals with postpoliomyelitis syndrome. Although additional research is needed to clarify the nature of the relationships between individual psychosocial variables and functional indices, the findings suggest the need for a multidisciplinary approach to pain management in individuals with postpoliomyelitis syndrome.